2015
DOI: 10.1007/978-3-319-16366-6_4
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Among Special Populations: Disparities in Care Across the Cancer Control Continuum

Abstract: Disparities in breast cancer risk factors, access, and treatment patterns are responsible for disparities in incidence, mortality and other measures of the impact of breast cancer among different population groups. Moreover, differences in culture and role definition impact various areas of aging and quality of life. Populations most impacted by disparities include women of racial/ethnic groups, older women, and women from rural and urban areas. More research is needed to document and address disparities acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…25 Future research is needed to understand whether rural cancer survivors have environmental and personal needs related to treatment and survivorship care, such as lack of access to health services or financial strain, that must be addressed prior to interpersonal support needs. 8 Our findings add to the evidence that an ecologic approach is needed to understand and change physical activity behavior in rural cancer survivors. Strengths of this study include the use of multiple measures of social support.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…25 Future research is needed to understand whether rural cancer survivors have environmental and personal needs related to treatment and survivorship care, such as lack of access to health services or financial strain, that must be addressed prior to interpersonal support needs. 8 Our findings add to the evidence that an ecologic approach is needed to understand and change physical activity behavior in rural cancer survivors. Strengths of this study include the use of multiple measures of social support.…”
Section: Discussionsupporting
confidence: 52%
“…3,4 Elevated psychosocial distress (eg, fear of recurrence, anxiety, depression) is not uncommon among cancer survivors and contributes to physical inactivity and poor quality of life among rural cancer survivors. 3,[5][6][7][8] Geographic isolation, inadequate transportation, and low access to health care and supportive oncology services and resources may contribute to rural-urban differences. 1,8,9 Social support is a coping resource and has been associated with reduced psychosocial distress and greater wellbeing among cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…week [8,12]. However, previous studies have found that rural cancer survivors are less likely to meet cancer-specific PA recommendations than urban cancer survivors [4,13,14]. Despite the overwhelming evidence supporting PA post-cancer diagnosis, more than half (50.7%) of rural cancer survivors report being physically inactive, or not doing any leisure-time PA lasting at least 10 minutes, compared to only 38.7% of urban cancer survivors [4].…”
Section: Introductionmentioning
confidence: 96%
“…There is also some evidence that rural residents are less likely to get screened for cancer (6): for example, an analysis of 2008 Behavioral Risk Factor Surveillance System (BRFSS) data showed that rural women were less likely to meet recommendations for mammography than urban women; that the proportion of women reporting appropriate cervical cancer screening decreased as rurality increased; and that individuals from rural areas were less likely to report colorectal cancer screening than individuals from urban areas (9). Furthermore, rural individuals may be less likely to receive follow-up testing after receiving abnormal screening results (10), and although findings are not consistent with regard to rural-urban differences in stage at diagnosis, some research suggests that women from rural areas are more likely to be diagnosed with more advanced breast cancer compared to their urban counterparts (11). …”
Section: Introductionmentioning
confidence: 99%